Design and testing of a steering damper for motorcycles based on a shear-thickening fluid. - Urda Gómez, Pedro; Pérez-Fernández, Javier; Carabias-Acosta, Enrique; Cabrera-Carrillo, Juan Antonio; Castillo-Aguilar, Juan Jesús (IOP, 2022)
This work is intended to show the feasibility of the utilisation of a shear-thickening fluid as working fluid in a steering damper for motorcycles. To that end, a prototype of a steering damper has been designed and then tested under different working conditions. Unlike conventional models, this new steering damper bases its performance on the combination of very simple rod geometries and a shear-thickening fluid of different concentrations. The experiments carried out with a test machine demonstrate that, despite its simplicity and reduced cost of manufacturing, the prototype shows similar behaviour to a conventional high-performance racing steering damper. The Bouc–Wen model has been used to reproduce the behaviour of the shear-thickening fluid-based damper prototype. The parameters of the model have been obtained following an optimization process to fit the model’s response to the experimental data when exciting the damper at different speeds. Results show that the damper’s behaviour can be properly modelled with a single combination of parameters.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/11350
Keywords: Fluidos no-newtonianos; Amortiguamiento (Mecánica); Vehículos de motor - Discpositivos de seguridad; Bouc–Wen model; Steering damper; Shear-thickening fluids; Motorcycle dynamics; Vehicle safety